Remittances in the CIS Countries : A Study of Selected Corridors - Quillin, Bryce (World Bank, Washington, DC, 2021)
The objective of this paper is to collect, organize and analyze information on remittance corridors from Russia to Armenia, the Kyrgyz Republic, Moldova and Tajikistan. It aims to provide an overview of the current framework and infrastructure for sending and receiving remittances, including aggregate flows, existing and potential operators, cost structures and, barriers and other factors affecting costs. Ultimately, it turns to setting out topics for policymakers' attention. Section one provides an overview of migration, remittances and financial sector developments; section two analyzes results from surveys undertaken with migrants who had returned in Georgia, the Kyrgyz Republic and Tajikistan (and uses as benchmarks, Bosnia-Herzegovina, Bulgaria and Romania); section three turns to the results of questionnaires and interviews with central banks, banks, Money Transfer Operators (MTOs), postal networks and other intermediaries; and section four turns to the emerging topics for policymaking.